Association between maternal anxiety/depression in pregnancy and the development of offspring eczema/AD: a meta-analysis based on cohort studies - Yu, Mengjiao; Zhang, Qiufeng; Chen, Junyi; Yang, Jingyu; Bai, Zhechuan; Wang, Junjie (Frontiers in Pediatrics, 2026)
BackgroundThis meta-analysis investigates the association between maternal anxiety/depression during pregnancy and the development of eczema/atopic dermatitis (AD) in offspring.MethodsA literature search was conducted across four electronic databases (PubMed, Web of Science, Embase, and the Cochrane Library) for studies published from database inception until July 2025. In this study, maternal depression and anxiety were defined as conditions physician-diagnosed or assessed with standardized scales during pregnancy. The primary outcome was the incidence of eczema/AD in the offspring.ResultA total of 12 cohort studies were included in this meta-analysis. Pooled results indicated that maternal depression [odds ratio (OR) = 1.06, 95% confidence interval (95% CI) = 1.01–1.11, p = 0.015] or anxiety (OR = 1.11, 95% CI = 1.03–1.19, p = 0.005) during pregnancy was potentially associated with a higher incidence of offspring eczema and AD. Subgroup analysis revealed that there was a higher incidence of AD in offspring with maternal anxiety during pregnancy (OR = 1.24, p = 0.028), while no significant difference was observed in the incidence of eczema (p = 0.286). A higher incidence of offspring eczema/AD was observed in offspring of both Eastern (OR = 1.13, p = 0.043) and Western (OR = 1.34, p = 0.049) countries. Moreover, the incidence was higher in offspring when maternal anxiety was identified in the first (OR = 1.13, p = 0.036) or second (OR = 1.25, p = 0.010) trimester, whereas no significant difference was found for exposure in the third trimester (p = 0.152). For maternal depression during pregnancy, offspring had a higher incidence of AD (OR = 1.17, p < 0.001), while no significant difference was observed for eczema (p = 0.145). Furthermore, the incidence of offspring eczema/AD was higher in Eastern countries (OR = 1.14, p = 0.035), while Western countries group showed no significant difference (p = 0.111). Additionally, when analyzed by timing of exposure, the incidence was higher when depression was identified in the second trimester (OR = 1.30, p = 0.027), with no significant difference found in the third trimester (p = 0.163).ConclusionThis study suggests that maternal depression/anxiety during pregnancy is potentially associated with the development of eczema/AD in offspring.